2014
DOI: 10.1093/hmg/ddu369
|View full text |Cite|
|
Sign up to set email alerts
|

Functional characterization of FABP3, 5 and 7 gene variants identified in schizophrenia and autism spectrum disorder and mouse behavioral studies

Abstract: Disturbances of lipid metabolism have been implicated in psychiatric illnesses. We previously reported an association between the gene for fatty acid binding protein 7 (FABP7) and schizophrenia. Furthermore, we identified and reported several rare non-synonymous polymorphisms of the brain-expressed genes FABP3, FABP5 and FABP7 from schizophrenia and autism spectrum disorder (ASD), diseases known to part share genetic architecture. Here, we conducted further studies to better understand the contribution these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 73 publications
1
66
0
Order By: Relevance
“…Interestingly, this selective impairment of social novelty preference has been reported across a broad range of animal models of schizophrenia (Kaminitz et al 2014; O'Tuathaigh et al 2007; Shimamoto et al 2014; Zoubovsky et al 2015, but O'Tuathaigh et al 2010a). Eagle and co-workers (Eagle et al 2013) proposed that this selective impairment might be related to the differences between sensation-seeking versus novelty-seeking behaviors, the latter requiring to recall and recognize a familiar versus a novel object.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, this selective impairment of social novelty preference has been reported across a broad range of animal models of schizophrenia (Kaminitz et al 2014; O'Tuathaigh et al 2007; Shimamoto et al 2014; Zoubovsky et al 2015, but O'Tuathaigh et al 2010a). Eagle and co-workers (Eagle et al 2013) proposed that this selective impairment might be related to the differences between sensation-seeking versus novelty-seeking behaviors, the latter requiring to recall and recognize a familiar versus a novel object.…”
Section: Discussionmentioning
confidence: 77%
“…We recently reported hyperactivity and anxiety‐related phenotypes in Fabp7 KO mice (Shimamoto et al, ). Consistently, here we found that total distance traveled (1,526 ± 113 cm in WT vs. 2,720 ± 107 cm in KO, P < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, gene expression of FABP3, FABP5, and FABP7 has been shown to be modulated in psychiatric illnesses such as schizophrenia and ASD [154]. In the brains of ASD patients, FABP7, which binds DHA preferentially, was upregulated in both the frontal and parietal cortex [155]. As in schizophrenic patients, PUFA distribution and metabolism are markedly altered in ASD patients.…”
Section: Risk Factors For Neuroinflammation and Autismmentioning
confidence: 99%